2015
DOI: 10.1186/s12913-015-1193-5
|View full text |Cite
|
Sign up to set email alerts
|

Seniors managing multiple medications: using mixed methods to view the home care safety lens

Abstract: BackgroundPatient safety is a national and international priority with medication safety earmarked as both a prevalent and high-risk area of concern. To date, medication safety research has focused overwhelmingly on institutional based care provided by paid healthcare professionals, which often has little applicability to the home care setting. This critical gap in our current understanding of medication safety in the home care sector is particularly evident with the elderly who often manage more than one chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 39 publications
3
28
0
2
Order By: Relevance
“…In such cases, they subsequently asked the GP to write a new prescription. This finding was supported by Lang et al, who also found that patient safety was affected by contextual challenges, which led the staff to devise workarounds to improve medication management despite system barriers, and that nurses needed literacy to navigate in the system to maintain medication safety in the home. In the present study, nurses devised workarounds by adapting their actions to the situation and the individual patient or colleague, rather than stringently adhering to regulations.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In such cases, they subsequently asked the GP to write a new prescription. This finding was supported by Lang et al, who also found that patient safety was affected by contextual challenges, which led the staff to devise workarounds to improve medication management despite system barriers, and that nurses needed literacy to navigate in the system to maintain medication safety in the home. In the present study, nurses devised workarounds by adapting their actions to the situation and the individual patient or colleague, rather than stringently adhering to regulations.…”
Section: Discussionmentioning
confidence: 81%
“…Although professionals were involved, we also found storage of medications unique for every household and a variety of systems put in place. We found, like Lang (35), that each home had 'its own system' for getting prescriptions filled, renewed and delivered, as well as for storage, packaging and taking of medications. McDonald et al (36) also raised the issue of blurred lines between where care ended and the home began, when care was moved into the home and changed the home into a care setting.…”
Section: Contextmentioning
confidence: 88%
“…Medication management during care transitions can have a positive impact on the clinical results of patients (34) . In a Canadian study (35) , there were reports of instructional failures and lack of understanding of patients regarding the purpose and effect of medications in use. Some patients did not remember receiving drug-related explanations, which resulted in unsafe medication usage.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 This innovative methodological approach adapts principles and methods from the field of ecological restoration to study safety issues in contemporary health systems from a socio-ecological perspective. 14,17,18 The theoretical rationale for a restorative research approach in health care safety is the premise that today's health care systems are over-fragmented complex adaptive systems that lack systemic integrity due to an imbalance between increasing technology and neglected ecology. 14,17 While the socio-ecological foundations of our restorative research approach constitute a different theoretical base than the critical social theoretical foundations of participatory action research (PAR), both methodological approaches are concerned with empowering communities to generate collective action for positive change.…”
Section: Introductionmentioning
confidence: 99%